2020
DOI: 10.1021/acs.jproteome.0c00493
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Metabolomics Analyses Reveal Specific Metabolic Alterations in High-Grade Prostate Cancer Patients

Abstract: Prostate cancer (PCa) is a hormone-dependent tumor characterized by an extremely heterogeneous prognosis. Despite recent advances in partially uncovering some of the biological processes involved in its progression, there is still an urgent need for identifying more accurate and specific prognostic procedures to differentiate between disease stages. In this context, targeted approaches, focused on mapping dysregulated metabolic pathways, could play a critical role in identifying the mechanisms driving tumorige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Another observation in our study was the presence of higher levels of tyrosine and phenylalanine in PCa and PCaB patients' serum when compared with BPH patients, respectively. It was substantiated by Gomez-Cebrian et al [42] that phenylalanine hydroxylase (PAH) is the enzyme that metabolizes excess phenylalanine into tyrosine; hence, it is also reported to have a direct association with protein acetylation and energy production [41,43]. Moreover, our study revealed that a decreased PAH expression might be directly proportional to the enhanced levels of both phenylalanine and tyrosine in PCa and its metastatic progression.…”
Section: Discussionsupporting
confidence: 68%
“…Another observation in our study was the presence of higher levels of tyrosine and phenylalanine in PCa and PCaB patients' serum when compared with BPH patients, respectively. It was substantiated by Gomez-Cebrian et al [42] that phenylalanine hydroxylase (PAH) is the enzyme that metabolizes excess phenylalanine into tyrosine; hence, it is also reported to have a direct association with protein acetylation and energy production [41,43]. Moreover, our study revealed that a decreased PAH expression might be directly proportional to the enhanced levels of both phenylalanine and tyrosine in PCa and its metastatic progression.…”
Section: Discussionsupporting
confidence: 68%
“…Furthermore, different systemic and local metabolic alterations have consistently been associated with PCa risk and progression [111][112][113][114][115][116]. In line with this, in a recent study by Gómez-Cebrián et al, the specific metabolomics profile of high-grade PCa patients was characterized on the basis of the alterations in metabolite levels identified in the serum and urine of PCa patients with different tumor grades [100]. A gene set enrichment analysis (GSEA) of three publicly available Pca transcriptomics datasets facilitated a targeted analysis of the metabolomics profiles, with a focus on metabolites involved in potentially altered metabolic pathways in high-grade Pca patients.…”
Section: Pca Subtypingmentioning
confidence: 79%
“…Three metabolic pathways, including fatty acid metabolism, TCA cycle, and glycerophospholipid metabolism, were upregulated in SPOP mutant tissues Oberhuber et al [ 130 ] Tissue M + P + T STAT3 low vs STAT3 high At the transcriptome level, OXPHOS is upregulated in PCa, as is the TCA cycle/OXPHOS at the proteome level. A promising independent prognostic marker in PCa is PDK4, a critical regulator of the TCA cycle Murphy et al [ 131 ] Tissue serum E + M + P + T BPH vs. PCa Higher accuracy in predicting PCa aggressiveness compared to clinical features alone or individual omics data with Ordinal C‐Index value of 0.94 and Multi AUC value of 0.91 Itkonen et al [ 132 ] Cell line M + P + T CDK9 inhibitor treated vs. untreated Inhibition of CDK9 causes acute metabolic stress in prostate cancer cells by consuming ATP and triggering rapid and sustained phosphorylation of AMPK, as well as dramatically downregulating oxidative phosphorylation in mitochondria and accumulation of acylcarnitines, metabolic intermediates in fatty acid oxidation Kamoun et al [ 133 ] Tissue E + G + T PCa vs. NAT A group of 36 transcriptomic biomarkers outperformed the most commonly used prognostic molecular signatures in identifying a subpopulation of patients without biochemical relapse Gómez et al [ 134 ] Urine serum M + T Low vs. high grade PCa Between the two groups of patients, there were significant changes in 36 metabolic pathways, including glycine, glucose, and 1-methlynicotinamide, metabolites important for energy metabolism and nucleotide synthesis Paez et al [ 135 ] Tissue P + T PRAD vs. NAT HO-1 is related with cellular cytoskeleton integrity, and its stimulation in PCa cells resulted in reduced cell trajectory and velocity, a lower frequency of migratory events, and a markedly increased proportion of filopodia-like protrusions that facilitate attachment between adjacent cells Sial et al [ 136 ] …”
Section: Multi Omicsmentioning
confidence: 99%